Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1136/bcr-2017-223637
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of concomitant metastatic prostate cancer and B-cell non-Hodgkin’s lymphoma with R-EPOCH chemotherapy regimen and antiandrogen therapy

Abstract: A 70-year-old man presented with left loin pain without urinary symptoms. Initial investigations with CT showed enlarged para-aortic, mediastinal lymph nodes, right-side renal mass and enlarged prostate. A prostatic-specific antigen (PSA) was alarmingly high at 4750 μg/L (normal <4.0 μg/L). Further investigations included positron emission tomography (PET); both prostate-specific membrane antigen and 18-fluorodeoxyglucose as well as bone scan and bone marrow examination confirmed dual malignancies with B-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…There is still no standard approach regarding the treatment regimen to be followed for cases with renal involvement. However, successful cases of treatment with the DA-EPOCH-R regimen have been reported in the literature [26,27]. In conclusion, renal involvement in DLBCL is rare, however, it is associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 93%
“…There is still no standard approach regarding the treatment regimen to be followed for cases with renal involvement. However, successful cases of treatment with the DA-EPOCH-R regimen have been reported in the literature [26,27]. In conclusion, renal involvement in DLBCL is rare, however, it is associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, de Souza et al pointed out that lymphoma may present as PSMA uptake after reviewing the data of 10 patients with different histological subtypes of lymphomas, and they subsequently found that the intensity of PSMA uptake was generally lower than FDG ( 11 ). Furthermore, several published case reports have also found that the PSMA expression of lymphoma was extremely low, or even had no expression ( 12 14 ). Thus, we deemed that the expression of PSMA on lymphoma was lower than adenocarcinoma, while the expression of FDG was higher.…”
Section: Discussionmentioning
confidence: 99%
“…In univariate analysis, we found that the dose of etoposide may affect the occurrence of neutropenia, but further inclusion in multivariate analysis revealed a nonsignificant effect on neutropenia. It is possible that although this study involved chemotherapy for multiple tumors, the dose distribution of etoposide was relatively concentrated regardless of the chemotherapy regimen [34][35][36]. Among the variables used to develop the nomogram in this study, KPS, comorbidity with heart disease, recent surgery, administration of alkylating agents, TBil ≥25 umol/L, and lymphocytes <0.7 × 10 9 /L have also been used in previous studies [5,8,9,18,37,38].…”
Section: Discussionmentioning
confidence: 99%